PENGARUH PROFITABILITAS, LIKUIDITAS, DAN FAKTOR LAINNYA TERHADAP NILAI PERUSAHAAN - MARLEN WILLIUS; SANTOSO CHANDRA (E-Jurnal Akuntansi TSM, 2021)
The purpose of this study is to obtain empirical evidence regarding the factors that influence the value of non-financial companies listed on the Indonesia Stock Exchange (BEI). The dependent variable in this study is firm value, the independent variables in this study are profitability, liquidity, managerial ownership, institutional ownership, company growth, and leverage. The object of this research is non-financial companies listed on the Indonesia Stock Exchange (BEI). The research sample used is as many as 85 companies with the 2017-2019 research period, so the data used is 255 data. Sampling using purposive sampling and the model in this study is multiple regression method. The measurement of firm value uses the price book value (PBV). The results obtained in this study are profitability, liquidity, managerial ownership, institutional ownership, company growth, and leverage have an effect on firm value